Home-Based Monitoring and Telemonitoring of Complicated Pregnancies: Nationwide Cross-Sectional Survey of Current Practice in the Netherlands - van den Heuvel, Josephus F M; Ayubi, Samira; Franx, Arie; Bekker, Mireille N (JMIR Publications, 2020)
BackgroundDaily monitoring of fetal and maternal conditions in complicated pregnancies leads to recurrent outpatient visits or (prolonged) hospitalization. Alternatives for hospital admissions include home-based monitoring with home visits by professionals or telemonitoring with self-measurements performed by pregnant women and uploaded for in-clinic assessment. For both alternatives, cardiotocography and blood pressure measurement can be performed at home. It is unknown to what extent, for which reasons, and for which pregnancy complications these strategies are used. ObjectiveThis study aims to assess the current practice and attitudes concerning home-based monitoring (with daily home visits by professionals) and telemonitoring (using devices and the internet for daily self-recorded measurements) in high-risk pregnancies requiring maternal and fetal monitoring in the Netherlands. MethodsThis nationwide cross-sectional study involved sending a web-based survey to the obstetrics departments of all 73 hospitals in the Netherlands to be answered by 1 representative dedicated to pregnancy monitoring per hospital. The primary outcome was the provision of home-based monitoring or telemonitoring using cardiotocography between 1995 and 2018. The survey further addressed perspectives regarding the use of home-based monitoring and telemonitoring, including (contra)indications, advantages, and disadvantages for pregnant women and clinicians. ResultsThe response rate for the provision of either home-based monitoring or telemonitoring was 100%. In 2018, 38% (28/73) of centers in the Netherlands offered either home-based monitoring or telemonitoring or both to pregnant women with complications. Home-based monitoring was offered in 26% (19/73) of the centers; telemonitoring, in 23% (17/73); and both in 11% (8/73). Telemonitoring was first offered in 2009, increasing from 4% (3/73) of hospitals in 2014 to 23% (17/73) in 2018. Responses were received from 78% (57/73) of the invited hospitals and analyzed. Of all 17 centers using telemonitoring, 59% (10/17) did not investigate perinatal outcomes, safety, and patient satisfaction prior to implementation. Other (6/17, 35%) telemonitoring centers are participating in an ongoing multicenter randomized clinical trial comparing patient safety, satisfaction, and costs of telemonitoring with standard hospital admission. Home-based monitoring and telemonitoring are provided for a wide range of complications, such as fetal growth restriction, pre-eclampsia, and preterm rupture of membranes. The respondents reported advantages of monitoring from home, such as reduced stress and increased rest for patients, and reduction of admission and possible reduction of costs. The stated barriers included lack of insurance reimbursement and possible technical issues. ConclusionsHome-based monitoring is provided in 26% (19/73) and telemonitoring, in 23% (17/73) of hospitals in the Netherlands to women with pregnancy complications. Altogether, 38% (28/73) of hospitals offer either home-based monitoring or telemonitoring or both as an alternative to hospital admission. Future research is warranted to assess safety and reimbursement issues before more widespread implementation of this practice.